1996
DOI: 10.1212/wnl.47.5.1284
|View full text |Cite
|
Sign up to set email alerts
|

Lenticular nucleus lesion in idiopathic dystonia detected by transcranial sonography

Abstract: We report the transcranial sonography (TCS) findings of the basal ganglia in 86 patients with dystonic disorders including idiopathic dystonia (facial, cervical, upper limb, and generalized dystonia), drug-induced tardive dystonia, dopa-responsive dystonia, and kinesigenic dystonia. The TCS was focused on alterations of the lenticular, caudate, raphe nuclei, and the thalamus. Seventy-five percent of patient with idiopathic cervical and 83% of those with idiopathic upper limb dystonia had a hyperechogenic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 10 publications
5
61
1
7
Order By: Relevance
“…Third-ventricle dilatation typically found already at early stages of progressive supranuclear palsy (Richardson syndrome) supports its discrimination from PD [31]. Hyperechogenicity of the lenticular nucleus is a characteristic finding in patients with generalized, segmental, focal and taskrelated forms of idiopathic dystonia [41,42]. However, the specificity of this TCS finding has been challenged by one study [44], and further studies are needed to assess its diagnostic value, e. g. for the discrimination of idiopathic dystonia from psychogenic movement disorders.…”
Section: Diagnostic Relevancementioning
confidence: 89%
See 1 more Smart Citation
“…Third-ventricle dilatation typically found already at early stages of progressive supranuclear palsy (Richardson syndrome) supports its discrimination from PD [31]. Hyperechogenicity of the lenticular nucleus is a characteristic finding in patients with generalized, segmental, focal and taskrelated forms of idiopathic dystonia [41,42]. However, the specificity of this TCS finding has been challenged by one study [44], and further studies are needed to assess its diagnostic value, e. g. for the discrimination of idiopathic dystonia from psychogenic movement disorders.…”
Section: Diagnostic Relevancementioning
confidence: 89%
“…The diagnosis of basal-ganglia hyperechogenicity is usually made visually [2]. In addition, hyperechogenic areas may be measured planimetrically, similar to measurements of SN hyperechogenicity [2,41]. Recently, the echo-intensity of basal ganglia was reliably quantified using digitized image analysis [12,42].…”
Section: Visualization and Assessmentmentioning
confidence: 99%
“…For example, lesions involving the caudate nucleus, putamen, globus pallidus, subthalamic nucleus, thalamus, and cerebellum have been associated with particular spontaneous dyskinesias in several studies using a variety of methodological techniques (e.g., Antonini et al, 1998;Dooling & Adams, 1975;Kim et al, 2002;Krystkowiak et al, 2000;Krystkowiak et al, 1998;LeDoux & Brady, 2003;Lehericy et al, 1996;Lenz et al, 2002;Lozza et al, 2002;Naumann et al, 1996;Perlmutter et al, 1997). Moreover, an array of structural and functional abnormalities have been observed in several of these regions in individuals with schizophrenia, although substantial variation in findings exists (e.g., Danos et al, 2002;Gunduz et al, 2002;Jernigan et al, 1991;Keshavan et al, 1998;Lang et al, 2001;Marcelis et al, 2003;McCreadie et al, 2002;Menon et al, 2001;Muller et al, 2002;Sigmundsson et al, 2001;Staal et al, 2000;Staal et al, 2001;Young et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia is characterized by involuntary prolonged muscle contractions that distort the body into typical postures 52,53 . The pathogenesis of idiopathic dystonia and their origin is still unknown.…”
Section: Dystoniamentioning
confidence: 99%
“…52 ). Subsequent studies 53 demonstrated that hyperechogenic LN is present in patients with torticollis or dystonic writer's cramp on the contralateral side of rotation of the head or aff ected hand.…”
Section: Dystoniamentioning
confidence: 99%